Living La Vida Loca? Remote Investing in Latin America, 1869-1929 - Gareth Campbell; Áine Gallagher; Richard S. Grossman (CESifo GmbH, 2024)
Substantial amounts of British capital flowed to Latin America during the latter part of the nineteenth and early twentieth centuries. Companies financed by this capital were typically headquartered in the UK, but operated thousands of miles away. This paper asks how this separation between governance and place of business affected the valuation of these firms. We find that the location of the headquarters played a more important role than the location of operations. Stock prices tended to fluctuate in line with other equities based in the UK, suggesting that they were still regarded as being, at least partially, British companies.
Keywords: F21; F54; F65; G11; G12; G15; G51; N16; N26; 330; Latin America; equity markets; portfolio investing; emerging markets